APPLICATION OF US-SCS CURVE NUMBER METHOD AND GIS FOR DETERMINING SUITABLE LAND COVER OF SMALL WATERSHED - Christanti Nana Widiyati; Sudibyakto Sudibyakto (Indonesian Journal of Geography, 2010)
This study aims to reveal the appropriate land cover which can reduce runoffusing US-SCS Curve Number method with GIS. Four land cover scenarios aredeveloped to reveal which one of existing land cover types is appropriate for thearea. To make a validation of the application US-SCS Curve Number Method,calculating observational run-off is required. Statistical analysis is than used totest those two run-off data. The result of this study shows that actual run-off depthis 2143, 0 mm and peak discharge is 91, 76 m3/s. The result also reveals that forestcoverage can reduce dramatically surface run-off until 48, 38 percent. Potatoincreases surface run-off 1, 59 percent, on the contrary, applying cacica papayacan reduce surface run-off 24, 6 percent. Scenario 4 is developed based on theresult of the previous scenario on run-off yield. Run-off yield result from scenario 4is 1690, 40 mm (decrease 21, 14 percent from actual run-off). Statistical analysisshows that there is no difference between observed run-off depth and estimatedrun-off depth in the level of significance 5 %.